Impact of Enhanced Lipid Peroxidation on Carotid Artery Intima Media Thickness Ratio in Patients Receiving Maintenance Hemodialysis - Rehman, Sadia; Mahboob, Tabassum; Kumar, Santosh; Ali, Syed Hidayat; Khan, Muhammad Tassaduq; Rehman, Suniya (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the impact of increased lipid peroxidation on carotid intima media thickness ratio in patients receiving maintenance hemodialysis.Study Design: Comparative prospective study.Place and Duration of Study: Jinnah Post Graduate Medical Center Karachi in collaboration with University of Karachi, Pakistan, from Jan to Dec 2018.Methodology: The hemodialysis patients were selected from the dialysis center where as the controls were recruited from normal healthy population. The cases taken were receiving maintenance hemodialysis thrice a week. Doppler ultrasonography technique was employed to detect the intima media thickness (IMT) ratio of common carotid artery of study subjects as well as controls. Lipid peroxidation was detected by serum oxidized LDL (ox-LDL) levels.Results: The mean of right common carotid artery of group A samples was 0.45 ± 0.04 mm, left common carotid artery was 0.42 ± 0.01mm, and mean intima thickness was 0.43 ± 0.02 mm, the mean of right common carotid artery in group B was 0.93 ± 0.09 mm and mean of left common carotid in group B was 1.07 ± 0.14 mm and mean intima thickness of group B samples was 1.0 ± 0.09 mm. In group A mean Ox-LDL was 24.87 ± 5.23 U/ml while in group C samples mean Ox-LDL was 73.77 ± 6.77 U/ml.Conclusion: Lipid peroxidation is much enhanced in patients on maintenance hemodialysis and leads to an increased carotid artery intima media thickness ratio which is a sign of development of atherosclerosis. This study will help the nephrologists in determining the causes..................